Insights from reading the Bible with the poor - Hall, Crystal L. (Insights (Minneapolis, Minn.), 2019)
In this volume, Crystal L. Hall, poverty scholar and Ph. D. candidate at Union Theological Seminary, introduces poverty studies and its importance to biblical scholars. She describes specific insights from her direct work with impoverished communities, offering particular examples alongside careful analyses of biblical texts that illustrate the exegetical insights gained from reading with the poor. She turns at last to challenges for the future of biblical interpretation in a world riven by inequality.